Partial replacement of skim milk with coconut milk for preparation of Dahi - Islam, Md Nurul; Khan, Akhi; Masum, A K M; Habib, Raihan (Fundamental and Applied Agriculture, 2016)
Dahi is a highly nutritious fermented dairy product. A number of research works has been done on dahi preparation, but very few works has been reported for preparation of dahi from skim milk replacing with different levels of coconut milk. So, the present study was conducted to measure the feasibility of partial replacement of skim milk with coconut milk in the manufacture of dahi. Five different types of dahi were prepared by replacing 0, 5, 10, 15 and 20% skim milk with coconut milk and the prepared dahi samples were designated as A, B, C, D and E type, respectively. The prepared dahi samples were subjected to physical, chemical and microbiological analysis to evaluate their qualities. Replacement of skim milk up to 10% with coconut milk increased total organoleptic score but score decreased when level of coconut milk was 15% and 20%. Dahi having 10% of coconut milk was better in terms of smell and taste. Dahi manufactured incorporating 5% coconut milk gave superior results for body and consistency and also for color and texture. Addition of coconut milk increased the total solids (g kg-1), fat (g kg-1), ash (g kg-1) and acidity (%) content but decreased the protein (g kg-1) and pH content. Dahi containing 5% coconut milk showed better performance with respect to chemical qualities other than control. Total bacterial count was higher in the dahi manufactured by replacement of coconut milk than control. From this study, it could be suggested that dahi might be successfully prepared by replacement of 5% and 10% skim milk with coconut milk.